PERANCANGAN WEBSITE BERBASIS INTERNET OF THINGS MENGUNAKAN FRAMEWROK FLASK - Saputra, Iwan Ganda; Ibrahim, Ibrahim (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2023)
A website is a page of information provided through the internet so that it can be accessed worldwide as long as it is connected to the internet network. A website is also a component or collection of components consisting of text, images, sound, and animation so that it is interesting to visit. The web consists of pages and collections of pages called homepages. Webset can also be created with the flask programming language. Flask is a micro web application framework written in Python and uses Werkzeug and Jinja2 dependencies. by creating a webset framework using bootsrap. because Bootstrap is an HTML, CSS, and Javascript framework that functions to design responsive websites quickly and easily.